2018
DOI: 10.6007/ijarbss/v8-i12/5762
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Financial Management Practices and Problems among Students

Abstract: Financially educated society tend to make better financial decisions. Nevertheless, individuals are seldom having a perfect financial knowledge. Behavioral economics admitted that individuals are not always rational and emotions can always affect decision making. Thus objectives of this paper are to investigate the financial problems among the students as well as their financial management practices. This is because the ability to manage personal finances has become increasingly important in both university an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
9
1
Order By: Relevance
“…First, and from a theoretical perspective, there are significant differences in the levels of EI and PT between university students and professionals in the financial industry that are associated with financial behavioral biases. Previous research has shown that EI and PT influence financial behavioral biases [6] and that university students present a gap in EI compared to professionals from other industries [11]. However, this is the first study to show that university students present a gap in EI and PTs compared to professionals in the financial industry and that this gap is related to some biases of the students' financial behavior.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…First, and from a theoretical perspective, there are significant differences in the levels of EI and PT between university students and professionals in the financial industry that are associated with financial behavioral biases. Previous research has shown that EI and PT influence financial behavioral biases [6] and that university students present a gap in EI compared to professionals from other industries [11]. However, this is the first study to show that university students present a gap in EI and PTs compared to professionals in the financial industry and that this gap is related to some biases of the students' financial behavior.…”
Section: Discussioncontrasting
confidence: 50%
“…In this regard, various criteria have been used to try to explain the factors that cause biases in financial behavior, highlighting among the most recent ones emotional intelligence (EI) and personality traits (PTs). On the one hand, high levels of EI have been shown to lead to superior employee performance [3][4][5] and the better financial performance of employees [6]. On the other hand, investor decisions and portfolio performance have also been found to be directly related to PTs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The author argued that by delaying paying bills, one accrues interest each day that the bill is not paid and interest adds up quickly, which makes the overall cost of the item(s) purchased much larger than the initial cost. An investigation on financial management practices and financial problems faced by University students revealed that students have good financial management practices but fail to meet their financial obligations due to low incomes to sustain their needs as they spend more time studying instead of finding a way to increase their income (Azer & Mohamad, 2018). Primary data was collected through a self-administered questionnaire among 369 University students in Malaysia.…”
Section: Personal Financial Management Practicesmentioning
confidence: 99%
“…In the current era of globalization, students, mostly from developing countries, travel to advanced countries to secure an education [28,29]. International students are careful when purchasing products and services in international markets [30].…”
Section: Cultural Services Cultural Products and Feelings Of Grounded...mentioning
confidence: 99%